2022
DOI: 10.3389/fvets.2022.901269
|View full text |Cite
|
Sign up to set email alerts
|

Small non-coding RNA landscape of extracellular vesicles from a post-traumatic model of equine osteoarthritis

Abstract: Extracellular vesicles comprise an as yet inadequately investigated intercellular communication pathway in the field of early osteoarthritis. We hypothesised that the small non-coding RNA expression pattern in synovial fluid and plasma would change during progression of experimental osteoarthritis. In this study, we conducted small RNA sequencing to provide a comprehensive overview of the temporal expression profiles of small non-coding transcripts carried by extracellular vesicles derived from plasma and syno… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 98 publications
2
25
0
Order By: Relevance
“…Exoview analysis specifically focuses on the exosomal population of EVs by using antibodies for surface tetraspanins such as CD9, CD81 and CD63. In this study and our previous study, we were able to show species cross reactivity with the CD9 and CD81 tetraspanins, but not CD63 ( 25 ). Exoview analysis demonstrated an increase in the number of exosomes after OA-induction surgery prior to MSC injection.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Exoview analysis specifically focuses on the exosomal population of EVs by using antibodies for surface tetraspanins such as CD9, CD81 and CD63. In this study and our previous study, we were able to show species cross reactivity with the CD9 and CD81 tetraspanins, but not CD63 ( 25 ). Exoview analysis demonstrated an increase in the number of exosomes after OA-induction surgery prior to MSC injection.…”
Section: Discussionsupporting
confidence: 77%
“…Day 18 was selected for MSC treatment to be administered to ensure an OA phenotype had developed within the joint as a response to surgical intervention. This was based on our previous study ( 25 ). The integrin α10-MSCs were thawed in a sterile water bath at 37°C, aspirated into a syringe through a 14G canula at a slow pace, and injected into the carpal joint of the OA-induced limb through a 20G canula over a minimum of 10 secs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results found that three miRNAs (miR-92a, miR-16 and miR-25) were significantly (FDR < 0.1) upregulated in the synovial fluid collected from horses with mild DIPJ OA compared to severe DIPJ OA. A post-traumatic equine carpal OA experimental model study also identified miR-92a in equine synovial fluid and reported miR-92a expression increased in extracellular vesicles derived from synovial fluid in early OA along with a panel of five other miRNAs (miR-23a, miR-25, miR-215, miR-486-5p and miR-451) [ 26 ]. Another equine study profiling miRNA in synovial fluid from the metacarpophalangeal joint showed miR-223 was significantly downregulated and miR-23b was significantly upregulated in the early OA group compared to the control group [ 25 ].…”
Section: Resultsmentioning
confidence: 99%
“…The first equine study to investigate small non-coding RNA signatures in early OA of equine synovial fluid found miR-223 was significantly downregulated in synovial fluid from the early OA group compared to the controls and miR-23b was significantly upregulated [ 25 ]. Furthermore, another equine study investigating small non-coding RNA extracellular vesicles in a post-traumatic OA model of the middle carpal joint discovered miR-23a was upregulated in the OA group compared to the control group [ 26 ]. Several human studies have demonstrated miR-23b is upregulated in OA cartilage compared to normal cartilage samples, with authors concluding the downregulation of miR-23b could be a potential therapeutic strategy for the treatment of OA [ 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%